DEVELOPMENT TENDENCIES OF THE RESIDENTIAL REAL ESTATE MARKET IN THE TERRITORIES OF THE REPUBLIC OF UZBEKISTAN (Marketing Journal, 2025)
This article systematically and scientifically analyzes the development trends of the residential real estate market in the regions of the Republic of Uzbekistan. The study deeply studied the growth rates of the housing market by region, demographic pressu re, urbanization processes, investment activity and the influence of state policy. As a result of empirical observations, the uneven development of the market between regions, regional differences in supply and demand, and the specific features of factors affecting price formation were identified. Also, the impact of mortgage lending, digitalization and infrastructure modernization on the housing market was analyzed, № 10-SON OKTA BR, 2025 -YIL 602 and scientific and practical recommendations were developed to balance regional development. The results of the study serve as an important scientific basis for improving housing policy and ensuring market stability.
Keywords: residential real estate; regional development; urbanization; mortgage lending; investment activity; market trends; price formation